The Cultural Ecology Representation in the Talempong Kayu Art of the Nagari Rangking Luluih Community, Solok Regency, West Sumatra - Septriani, septriani (Institut Seni Indonesia Padangpanjang, 2024)
This research examines one cultural element in the form of talempong kayu art. There are seven elements of universal culture, one of which is art. Talempong is a typical Minangkabau art that has been passed down from generation to generation, one of which is in Nagari Rangking Luluih, West Sumatra. However, this talempong is different from talempong in general. Talempong is usually made of brass, tin and copper. Meanwhile, the talempong in Nagari Rangking Luluih is made of wood so it is called talempong kayu. Talempong kayu is no longer played much in West Sumatra. In general, Minang people play talempong which is made of copper and brass. However, in Rangking Luluih talempong kayu still exists and is often played on several occasions, especially during ritual ceremonies. Therefore, the aim of this research is to examine in more depth the talempong kayu representation, especially the background to its creation and the manufacturing process. The methods used in this research are direct observation, in-depth interviews and documentation. The research results showed that in talempong kayu there is a reciprocal relationship between humans and nature in the process of creating a culture, as stated in cultural ecology. Talempong kayu is not only an art, but it also contains people's knowledge and technology about the surrounding natural environment so that talempong kayu can fulfill people's needs for beautiful sounds and rituals of gratitude for sufficient harvests and a good life. This ritual must be carried out as a form of harmonious human relationship with the natural environment.